Rearrange the first equation until you have y written as some function of x, then plug the answer you have for y into the second equation. Now you can solve that equation for x. Then take your new value for x and sub it into either equation. You will get your value of y.
Here are the steps:
-6x + y= -12 (1)
7x+8y=14 (2)
Rearrange (1):
y = -6 (2+x)
Plug into (2)
7x+8(-6(2+x))=14 -> 7x-48(2+x) = 14 -> 7x-96+48x=14 -> 55x = 110
Thus, x = 2.
Take this value of x and plug it into either equation. It will generate a value for y.
Plug x = 2 into (1):
-6(2)+y=-12
Therefore, y = 0.
Done.
-10
It is also x = 5 8zx + 5 = 2j + 3 → 8zx + 2 = 2j → 4zx + 1 = j Which is the first equation, which has a solution x = 5.
The solution
The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)
The second equation is not complete and there is not sufficient information for a solution. It would make no sense for me to guess what a + b equals since, in that case, I may as well start posting my own questions and answering them!
There is one solution. To find it, divide both sides of the equation by 2. This leaves you with x=5, where 5 is your solution.
-10
It is also x = 5 8zx + 5 = 2j + 3 → 8zx + 2 = 2j → 4zx + 1 = j Which is the first equation, which has a solution x = 5.
Nobody can help you find a solution until you get another equation to go along with this one. Your equation has two variables in it ... 'x' and 'y' ... so it has no unique solution all by itself.
(Since 5 times 20 does equal 100, the solution is correct.
The solution
The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)The idea is to find a number which, when square, equals the given number. For example, asking for the square root of 100 means solving the equation x2 = 100. The solution, in this case, is 10. (Minus 10 is also a solution, but the term "square root" refers to the positive solution in this case.)
The second equation is not complete and there is not sufficient information for a solution. It would make no sense for me to guess what a + b equals since, in that case, I may as well start posting my own questions and answering them!
This is an equation of a straight line. A solution for two unknowns requires two (independent) equations; there is only one here. Every point that is on that line is a solution to the equation. So you can let x be any real number and find a corresponding y. This ordered pair (x,y) will be a solution to the equation as well as a point on the graph of the line.
To find the solution to this equation, you need to rearrange the terms and solve for the variable. 4 = 2b + b^2 can be rewritten as b^2 + 2b - 4 = 0. You can then solve this quadratic equation by factoring, completing the square, or using the quadratic formula.
The easiest way to solve this system of equations is to solve for a variable in one of the equations. In the second equation, y = 3x. This can be substituted into the first equation: y = -4x - 7; 3x = = -4x - 7; 7x = -7; x = -1. Since we have determined that x equals -1, we can then substitute -1 into either equation to find our corresponding y-value. Thus: y = 3x; y = 3(-1) y = -3. Thus, the solution to this system of equations is (-1, -3).
No. There is not enough information in the equation x + 2y = 2, by itself, to solve it. There are an infinite number of solutions. A second equation, or information to allow a second equation to be derived, must be given to find a solution.